A Potential Animal Model of Maladaptive Palatable Food Consumption Followed by Delayed Discomfort - Moshe, Lital; Bekker, Liza; Weller, Aron (Frontiers in Neuroscience, 2017)
Bingeing is the consumption of larger amounts of food in a briefer period of time than would normally be consumed under similar circumstances. Bingeing requires palatable food (PF) to trigger abnormal eating, probably reflecting gene x environment interactions. In this study we examined the impact of trait binge eating (BE) and its compulsive nature on the conflict between hedonic eating of PF and anticipation of a delayed aversive effect. We used female rats as an animal model similar to other models of BE. A novel aspect of this model in this paper is the use of a delayed internal aversive effect produced by lactose ingestion. Establishing this model will allow us to better understand the nature of the conflict between immediate reward and its delayed aversive implications. We hypothesized that BE prone (BEP) rats will demonstrate maladaptive decision making, presenting higher motivation toward PF even when this is associated with delayed discomfort. Method: (Phase 1) 52 female adult Wistar rats were divided to two eating profiles: resistant and prone binge eaters (BER/BEP) based on intake of liquid PF (Ensure). Next, all subjects underwent a Lactose Conditioning Protocol (LCP) that included 4hr tests, one baseline and 3 conditioning days (Phase 2), in which solid PF (Oreo cookies) was paired with glucose (control-no internal aversive effect) or lactose, dissolved in liquid PF. Index for PF motivation was PF consumption during the 4hr LCP. To test for memory of lactose conditioning, we performed another LCP with glucose only (anticipation, but no actual lactose-induced discomfort), a week after the last conditioning session. Results: Lactose conditioned BEP showed higher motivation toward PF compared to lactose conditioned BER faced with delayed aversive effects. Only lactose conditioned BER rats devaluated the PF over LCP days, indicating an association between PF and abdominal discomfort. In addition, only lactose conditioned BER presented an adaptive dynamic behavior, by varying PF intake according to consequences. Furthermore, solid PF consumption was predicted by binge size of liquid PF, only for lactose conditioned rats. Conclusions: We established an animal model for a common eating conflict in humans using delayed internal aversive unconditional stimuli.